2021
DOI: 10.1101/2021.03.08.21253120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post discharge persistent symptoms after COVID-19 in rheumatic and musculoskeletal diseases

Abstract: OBJECTIVES: To describe persistent symptoms and consequences in Rheumatic and Musculoskeletal diseases (RMD) discharged from the hospital after Covid-19; to assess the roll of autoimmune rheumatic diseases (ARD) compared to and non-autoimmune rheumatic and musculoskeletal diseases (NARD) on persistent symptoms and consequences. METHODS: We performed a cross-sectional observational study. RMD attended at a rheumatology outpatient clinic in Madrid with Covid-19 that required hospital admission were included. Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In the manual search of gray literature and preprints, 18 potentially related papers were included. After reviewing the titles and abstracts of the articles, 157 peer-reviewed papers or preprinted manuscripts were reviewed and a total of 91 articles were entered into the present meta-analysis [ 8 , [14] , [15] , [16] , [17] , [18] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ,…”
Section: Resultsmentioning
confidence: 99%
“…In the manual search of gray literature and preprints, 18 potentially related papers were included. After reviewing the titles and abstracts of the articles, 157 peer-reviewed papers or preprinted manuscripts were reviewed and a total of 91 articles were entered into the present meta-analysis [ 8 , [14] , [15] , [16] , [17] , [18] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ,…”
Section: Resultsmentioning
confidence: 99%
“…Global patient-reported disease activity was worse at the time of survey than before COVID-19 (mean 6.6±2.9 vs. 7.6±2.3, p<0.001). Median time to COVID-19 symptom resolution was 14 days (IQR 9,29).…”
Section: Resultsmentioning
confidence: 99%
“…An early study surveyed 105 rheumatology participants in Spain who had been hospitalized with COVID-19 and classified them as having SARDs (n=54) or non-autoimmune rheumatic conditions (n=51, such as osteoarthritis)(29). Similar to our study, they found that a high proportion of subjects had lingering symptoms (some lasting for over 90 days) that included dyspnea, fatigue, chest pain, and cough.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of PASC remains unknown but several factors have been hypothesized to influence risk, including alterations in inflammatory cytokine profiles, cellular immune responses, reactivation of chronic viral infections, and autoantibody formation. [35][36][37][38][39][40][41] Vaccination may reduce the risk of PASC by shortening the duration of viremia, reducing the risk of severe COVID-19 and the associated hyperinflammatory state, influencing the cellular immune response to acute infection, among other possible explanations.…”
Section: Discussionmentioning
confidence: 99%